02 The emergence ofthe Sufiliteratureasthe balance ofpower in Media - Abbas MOHAMMADIAN; Ali SADEGHIMANESH (Association of Social and Educational Innovation, 2015)
The present study is about the impact of Sufi literature onthe emergence ofthe emancipated Media in Iran. Literature was the most powerful media, when there was not television, radio and internet. As, media is an important tool for maintaining the legitimation of regimes, rulers were trying to make a powerful control on poetry and poets. Economic conditions, publishing and distribution situation and the other limitations were the reason of poets' dependence on the rulers. The emergence ofSufiliteraturewas asthe balance ofpower inmedia. Sufi poets were so powerful, so they did not have to obey the rulers. Sanaee was the first raised Sufi poet that freed poetry from ruler's control and balanced the power of Media.